PERAN POLISI WANITA DALAM MODERASI BERAGAMA DI INDONESIA - Kamdani, Kamdani (Studia Sosia Religia, 2026)
Religious moderation has become a national strategic agenda in Indonesia aimed at maintaining social harmony within a pluralistic society. This policy emphasizes the balance between commitment to religious teachings and respect for diverse religious practices. This study aims to examine the contribution of a gender perspective, particularly the role of Policewomen (Polwan), in strengthening religious moderation in Indonesia. Employing a qualitative descriptive-analytical approach, this research adopts a normative legal method through a literature review of academic sources, policy documents, and relevant legal regulations. The findings reveal that Policewomen occupy a strategic position in promoting religious moderation through a human-centered, communicative, and persuasive policing approach. The involvement of Policewomen and female community police officers (Bhabinkamtibmas) in community engagement, social mediation, and the security of interfaith religious activities significantly contributes to strengthening national commitment, tolerance, non-violence, and accommodation of local culture. This study concludes that optimizing the role of Policewomen not only advances gender equality within the police institution but also serves as a vital instrument for translating religious moderation from policy discourse into concrete practices at the grassroots level.